La survie des entreprises privées en difficulté au regard du droit international économique : le préjudice comme condition d'intervention de l'État - Bernier, Ivan (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
The present article examines, in the light of recent trends in international economic law, the various means offered to States for protecting their industries threatened by imports. What comes out most clearly from this inquiry is the growing importance of the concept of prejudice as a legal justification for State protectionism, a development which, if not obvious, is nevertheless changing in depth the original structure of the General Agreement on Tarifs and Trade. Among other consequences, this tendency to make State intervention dependent upon a finding of serious prejudice favors the development, at the national level, of quasi-judicial organs specialised in the field of international trade, each with their own distinct interpretation of what constituted a prejudice and of the link of causality required to justify limiting imports. Such a development, however dangerous it may be to international trade, offers at least a minimum of transparency as far as State protectionism is concerned and can simply not be ignored by private enterprises.